2001
DOI: 10.1034/j.1600-0447.2001.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about the optimal duration of prophylactic antipsychotic medication in schizophrenia: evidence and arguments

Abstract: Since rehabilitation efforts have effects only after long-term endeavours, antipsychotic relapse prevention should be maintained for long periods. It is reasonable to treat patients suffering from schizophrenia and related psychoses for longer periods than indicated by the current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Importantly, the risk of relapse was relatively stable during the 3-year follow-up period, indicating that, despite achieving remission, treatment of schizophrenia must be maintained long-term. 22 We found that duration of illness influenced both remission and relapse: a longer duration of illness was associated with a lower risk of remission and of relapse. These results confirm that schizophrenia, over the long-term, tends to have a deteriorating course in which remission is more and more infrequent, but also that patients with schizophrenia have fewer and less severe relapses.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, the risk of relapse was relatively stable during the 3-year follow-up period, indicating that, despite achieving remission, treatment of schizophrenia must be maintained long-term. 22 We found that duration of illness influenced both remission and relapse: a longer duration of illness was associated with a lower risk of remission and of relapse. These results confirm that schizophrenia, over the long-term, tends to have a deteriorating course in which remission is more and more infrequent, but also that patients with schizophrenia have fewer and less severe relapses.…”
Section: Discussionmentioning
confidence: 94%
“…Better treatment adherence could have an impact on reducing the frequency of relapses (Kane et al, 1998) which may, in turn, reduce the cost of treatment by reducing the length of hospitalization with concomitant improvement in the overall disability in these patients (Knapp et al, 2002;Patel et al, 2003). However, not all the depot antipsychotics are equally effective (Coutinho et al, 2000;Quraishi and David, 2001) and there is some evidence suggesting that the relapses may be unpredictable even with depot maintenance treatment (Bosveld-van Haandel et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…The most important interventions for first episode psychosis are: accurate diagnostic assessment, initiating antipsychotic medication as soon as it is feasible, and continuation of antipsychotic treatment after response for at least one year in the APA guidelines and at least two years in the Dutch guidelines. The recommended duration of antipsychotic prophylaxis in the Dutch guidelines is one year longer, because relapse rates do not seem to level off during the first years after remission from a first episode [17]. …”
Section: Introductionmentioning
confidence: 99%